2019
DOI: 10.18554/reas.v7i2.2987
|View full text |Cite
|
Sign up to set email alerts
|

Domínios Afetados Na Qualidade De Vida Do Paciente Renal Crônico Em Tratamento Hemodialítico: Revisão Sistemática

Abstract: Objetivo: Sintetizar o conhecimento produzido acerca das publicações na literatura nacional e internacional sobre os domínios afetados na qualidade de vida dos pacientes renais crônicos em tratamento hemodialítico. Método: Foi realizada uma revisão sistemática nas bases de dados, LILACS, MEDLINE e CINAHL, nos últimos 10 anos. Resultados: Foram analisados 9 artigos, a maioria dos estudos eram descritivos e transversais, apresentaram evidências sobre as relações das dimensões afetadas na qualidade de vida dos in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
0
2
0
13
Order By: Relevance
“…Subsequently, the abstracts of the selected articles were analyzed by two independent judges, considering the following exclusion criteria: duplicate documents; works that had been published outside the established period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017); works that are not directly related to the theme of adherence to treatment of chronic renal patients undergoing hemodialysis or peritoneal dialysis treatment; those that failed to answer the pre-defined guiding question; "gray literature"-book chapters, news, technical papers, comments, editorials, dissertations, and thesis; and restricted access (not free). Other studies served to deepen the discussion with those found in this article (Evangelista et al 2019;Gomes et al 2019).…”
Section: Search Strategies: Database and Inclusion And Exclusion Critmentioning
confidence: 76%
See 1 more Smart Citation
“…Subsequently, the abstracts of the selected articles were analyzed by two independent judges, considering the following exclusion criteria: duplicate documents; works that had been published outside the established period (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017); works that are not directly related to the theme of adherence to treatment of chronic renal patients undergoing hemodialysis or peritoneal dialysis treatment; those that failed to answer the pre-defined guiding question; "gray literature"-book chapters, news, technical papers, comments, editorials, dissertations, and thesis; and restricted access (not free). Other studies served to deepen the discussion with those found in this article (Evangelista et al 2019;Gomes et al 2019).…”
Section: Search Strategies: Database and Inclusion And Exclusion Critmentioning
confidence: 76%
“…They reach a consensus on the results of their research in regard to family support, suggesting that through this, the patient feels supported and welcomed, enabling greater engagement with the treatment. Also about quality of life, in their review, Evangelista et al (2019) point out that the measurement of this construct provides important data, especially on psychological and social spheres that affect the patient with chronic kidney disease, because even with health services quality of care improvement, increase in patients life expectancy, and technological advances of different treatment modalities, a reduction in the quality of life of these patients was identified, besides significant impacts on daily life.…”
Section: Psychosocial Factors Associated With Treatment Adherence In mentioning
confidence: 99%
“…Dentre tais alternativas, o tratamento de hemodiálise é o mais utilizado, pois é realizado por uma máquina que substitui a função renal (Evangelista et al, 2018).…”
Section: Introductionunclassified
“…3 Caracteriza-se, também, a DRC pela perda irreversível da função renal e/ou pela redução funcional renal presente, por um período igual ou maior a três meses, evidenciadas por alterações sanguíneas, urinárias ou em exames de imagem. [4][5] Acrescenta-se que, muitas vezes, pode ser causada pela Hipertensão Arterial (35,00%), seguida da Diabetes Mellitus (29,00%). [3][4][5][6] Sabe-se que o diagnóstico da DRC precoce possibilita o tratamento conservador por meio de restrições alimentares e do uso de medicações para o controle da doença de base, o que permite a não progressão da doença renal.…”
unclassified
“…[4][5] Acrescenta-se que, muitas vezes, pode ser causada pela Hipertensão Arterial (35,00%), seguida da Diabetes Mellitus (29,00%). [3][4][5][6] Sabe-se que o diagnóstico da DRC precoce possibilita o tratamento conservador por meio de restrições alimentares e do uso de medicações para o controle da doença de base, o que permite a não progressão da doença renal. 7 Pode-se, com a evolução da doença, instituir outras formas de tratamento, tais como o transplante renal e os processos dialíticos, que incluem a Diálise Peritoneal Ambulatorial Contínua (CAPD), Diálise Peritoneal Automática (DPA), Diálise Peritoneal Intermitente (DPI) e a Hemodiálise (HD), sendo esta a forma terapêutica mais utilizada.…”
unclassified